2021
DOI: 10.3390/ani11010097
|View full text |Cite
|
Sign up to set email alerts
|

Salinity, Temperature and Ammonia Acute Stress Response in Seabream (Sparus aurata) Juveniles: A Multidisciplinary Study

Abstract: The present study aimed to investigate the acute response of gilthead seabream (Sparus aurata) juveniles exposed to temperature, salinity and ammonia stress. Radioimmunoassay was used to evaluate cortisol levels, whereas insulin-like growth factors (igf1 and igf2), myostatin (mstn), heat-shock protein 70 (hsp70) and glucocorticoid receptor (gr) gene expression was assessed trough Real-Time PCR. The presence and localization of IGF-I and HSP70 were investigated by immunohistochemistry. In all the stress conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 107 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…Cheng et al reported that environmental ammonia stress altered the Hsp70 and Hsp90 transcription in Takifugu obscurus [ 31 ]. Hsp70 is known to be involved in stress response, intracellular trafficking, anti-apoptosis, antigen processing or chaperone functions [ 108 , 109 ]. Hsp90 is usually present in a constitutively dimmable manner and functions critically in the control of multiple regulatory pathways, for example, stress defense, hormonal signaling, cell cycle control, cell proliferation and differentiation, and apoptosis [ 110 ].…”
Section: Immune Responsementioning
confidence: 99%
“…Cheng et al reported that environmental ammonia stress altered the Hsp70 and Hsp90 transcription in Takifugu obscurus [ 31 ]. Hsp70 is known to be involved in stress response, intracellular trafficking, anti-apoptosis, antigen processing or chaperone functions [ 108 , 109 ]. Hsp90 is usually present in a constitutively dimmable manner and functions critically in the control of multiple regulatory pathways, for example, stress defense, hormonal signaling, cell cycle control, cell proliferation and differentiation, and apoptosis [ 110 ].…”
Section: Immune Responsementioning
confidence: 99%
“…In the present study, there was a general trend to lower levels of igf2 compared to control fish in brain, which was also observed in the other organs after either treatment. Lower igf2 in contrast to igf1 gene expressions were also observed in seabream juveniles (Sparus aurata) one hour after stress conditions of salinity, temperature and ammonia, whereby igf1 was emphasized to be more under control of Gh ( 76 ). Organ specific alterations of igf1 and igf2 after Gh treatment were observed in rainbow trout ( Oncorhynchus mykiss ) ( 77 ), Nile tilapia pituitary and immune organs ( 28 , 43 ).…”
Section: Discussionmentioning
confidence: 91%
“…The results are in line with various studies that concluded the negative impact of hypersalinity on the growth behavior of common carp (Iffat et al, 2021; Naskar et al, 2021). The reduction of growth performance is associated with the disturbance of osmoregulation and homeostasis function that consumes high energy levels, leading to impaired metabolic function (Toh et al, 2011; Zarantoniello et al, 2021). The reduction of growth behavior and feed utilization in common carp stressed with the high salinity in this study is probably correlated with increased Na + /K + ‐ATPase (Huang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%